Cancer Diagnostic Delay in Northern and Central Italy During the 2020 Lockdown Due to the Coronavirus Disease 2019 Pandemic: Assessment of the Magnitude of the Problem and Proposals for Corrective Actions. Issue 1 (30th September 2020) - Ferrara, Gerardo; De Vincentiis, Ludovica; Ambrosini-Spaltro, Andrea; Barbareschi, Mattia; Bertolini, Valentina; Contato, Edgardo; Crivelli, Filippo; Feyles, Elda; Mariani, Maria Paola; Morelli, Luca; Orvieto, Enrico; Pacella, Elena; et al.
Abstract: Objectives: We performed data collection concerning the coronavirus disease 2019 (COVID-19) pandemic-related delay in the diagnosis of cancers to individuate proper corrective procedures. Methods: A comparison was made among the number of first pathologic diagnoses of malignancy made from weeks 11 to 20 of 2018, 2019, and 2020 at seven anatomic pathology units serving secondary care hospitals in northern-central Italy. Results: Cancer diagnoses fell in 2020 by 44.9% compared with the average number recorded in 2018 and 2019. Melanoma and nonmelanoma skin cancer represented 56.7% of all missing diagnoses. The diagnostic decrease in colorectal (–46.6%), prostate (–45%), and bladder (–43.6%) cancer was the most relevant among internal malignancies; for prostate, however, high-grade tumors were only moderately affected (–21.7%). Conclusions: Diagnosis of cutaneous malignancies was mostly affected by the lockdown; among internal malignancies, corrective actions were mostly needed for colorectal cancer and invasive bladder cancer.